A Comprehensive Genetic and Bioinformatic Analysis Provides Evidence for the Engagement of COVID-19 GWAS-Significant Loci in the Molecular Mechanisms of Coronary Artery Disease and Stroke - Alexey Loktionov; Ksenia Kobzeva; Anna Dorofeeva; Maryana Babkina; Elizaveta Kolodezhnaya; Olga Bushueva (MDPI AG, 2024)
Cardiovascular diseases (CVDs) significantly exacerbate the severity and mortality of COVID-19. We aimed to investigate whether GWAS-significant SNPs correlate with CVDs in severe COVID-19 patients. DNA samples from 199 patients with severe COVID-19 hospitalized in intensive care units were genotyped using probe-based PCR for 10 GWAS SNPs previously implicated in severe COVID-19 outcomes. SNPs rs17713054 SLC6A20-LZTFL1 (risk allele A, OR = 2.14, 95% CI 1.06-4.36, p = 0.03), rs12610495 DPP9 (risk allele G, OR = 1.69, 95% CI 1.02-2.81, p = 0.04), and rs7949972 ELF5 (risk allele T, OR = 2.57, 95% CI 1.43-4.61, p = 0.0009) were associated with increased risk of coronary artery disease (CAD). SNPs rs7949972 ELF5 (OR = 2.67, 95% CI 1.38-5.19, p = 0.003) and rs61882275 ELF5 (risk allele A, OR = 1.98, 95% CI 1.14-3.45, p = 0.01) were linked to a higher risk of cerebral stroke (CS). No associations were observed with AH. Bioinformatics analysis revealed the involvement of GWAS-significant loci in atherosclerosis, inflammation, oxidative stress, angiogenesis, and apoptosis, which provides evidence of their role in the molecular mechanisms of CVDs. This study provides novel insights into the associations between GWAS-identified SNPs and the risk of CAD and CS.